2002
DOI: 10.1002/pd.375
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal identification of esophageal atresia: the role of ultrasonography for evaluation of functional anatomy

Abstract: Our three-sectional view of the neck and upper chest is useful for in utero detection of esophageal pouch that may enhance the prenatal diagnosis of EA. The positive predictive value for prenatal ultrasound for detecting EA is 100% with a sensitivity of 80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 12 publications
1
48
0
6
Order By: Relevance
“…The branchial arches contribute extensively to the growth of the face, oronasal cavities, palate, larynx, pharynx, and neck. 6 Congenital abnormalities of the fetal neck include those associated with fetal aneuploidies (cystic hygroma 7,8 ), the presence of embryologic remnants (thyroglossal duct and branchial cleft cysts [9][10][11][12] ), primary structural abnormalities (laryngeal cysts/ stenosis/atresia, [13][14][15][16][17] proximal esophageal atresia, 18 and bronchogenic cysts 19 ), functional abnormalities (goiters 20,21 ), benign tumors (lymphangioma, 22,23 hemangioma, 24 hemangiopericytoma, 25 and teratoma [26][27][28] ), malignant tumors (neuroblastoma 29 and rhabdomyoma 30,31 ), and an extensive array of syndromes (including Schinzel-Giedion, Yunis-Varon, and Escobar syndromes 32 ). In addition, subtle soft tissue changes of the upper posterior aspect of the fetal neck have been used in the second-trimester detection of trisomy 21 (nuchal thickness 33 Currently, a relative paucity of literature exists pertaining to precise sonographic measurements of the fetal neck.…”
Section: Discussionmentioning
confidence: 99%
“…The branchial arches contribute extensively to the growth of the face, oronasal cavities, palate, larynx, pharynx, and neck. 6 Congenital abnormalities of the fetal neck include those associated with fetal aneuploidies (cystic hygroma 7,8 ), the presence of embryologic remnants (thyroglossal duct and branchial cleft cysts [9][10][11][12] ), primary structural abnormalities (laryngeal cysts/ stenosis/atresia, [13][14][15][16][17] proximal esophageal atresia, 18 and bronchogenic cysts 19 ), functional abnormalities (goiters 20,21 ), benign tumors (lymphangioma, 22,23 hemangioma, 24 hemangiopericytoma, 25 and teratoma [26][27][28] ), malignant tumors (neuroblastoma 29 and rhabdomyoma 30,31 ), and an extensive array of syndromes (including Schinzel-Giedion, Yunis-Varon, and Escobar syndromes 32 ). In addition, subtle soft tissue changes of the upper posterior aspect of the fetal neck have been used in the second-trimester detection of trisomy 21 (nuchal thickness 33 Currently, a relative paucity of literature exists pertaining to precise sonographic measurements of the fetal neck.…”
Section: Discussionmentioning
confidence: 99%
“…Polyhydraminos alone is a poor indication of oesophageal atresia (1% incidence). Available methods of improving the prenatal diagnostic rate include ultrasound examination of the fetal neck to view the blind-ending upper pouch [16] and to observe fetal swallowing and magnetic resonance imaging [17]. …”
Section: Clinical Description and Diagnosismentioning
confidence: 99%
“…In recent decades, prenatal visualization of the proximal esophageal pouch has received increasing interest18–22 because of its high specificity in the diagnosis of esophageal atresia19, 20. It has also been suggested that the level of the pouch may be of prognostic value23, 24. The accuracy of the prenatal diagnosis of esophageal atresia might be further improved by three‐dimensional (3D) ultrasound25 and by MRI26.…”
Section: Introductionmentioning
confidence: 99%